Comparison of prompting procedures to teach internet skills to older adults. Issue 1 (26th October 2018) - Pachis, Jacqueline A.; Zonneveld, Kimberley L. M.
Abstract : The Internet and information and communications technologies (ICTs) have been found to produce meaningful social interactions and greater social support among older adults (White et al., 2002 ). Despite these benefits, the Internet and ICTs are not widely used among the older‐adult population (Cresci, Yarandi, & Morrell, 2010 ). The purpose of the current study was to compare the effectiveness and efficiency of video prompting and text‐based instructions on the acquisition of three tablet‐based tasks: emailing, video calling (FaceTime® application), and searching for a YouTube™ video. Both video prompting and text‐based instructions were effective for all three participants, with text‐based instructions being slightly more efficient for one participant and video prompting being more efficient for two participants, suggesting that both prompting procedures can be used to teach older adults Internet and ICT skills.